Statistics and construction methods for deep TBM tunnels with high geostress: A case study of Qinling Tunnel in Hanjiang-Weihe River Diversion Project. (August 2022) - Han, Xingbo; Liang, Xiaoming; Ye, Fei; Wang, Xin; Chen, Ziming
Highlights: Detailed rockburst site statistics. A field data based rockburst classification and mechanism analysis. Construction countermeasures for rockburst sections of a TBM tunnel. Abstract: Rockbursts pose serious threats to the engineering safety. As a typical deep TBM tunnel with high geostress, the Qinling Tunnel of Hanjiang-Weihe River Diversion Project has encountered a large number of rockbursts. Based on this project, a detailed analysis of the rockburst data was used to investigate the size and locations of single rockfalls, and volume of a single blast. Moreover, the relationships between rockbursts and lithology, and between rockbursts and buried depth were established, and the form of rockburst damage was analysed. In addition, specific construction methods under different rockburst levels were summarised, drawing on the successful experience of this project. A method for replacing the cutter head under rockburst risk after long-distance tunnelling was also proposed.